Anomalous Sediment Consolidation and Alteration From Buried Incoming Plate Seamounts Along the Cascadia Margin - Michelle K. Lee; Suzanne M. Carbotte; Shuoshuo Han; Brandon Shuck; Pinar Gurun; Brian Boston; Mladen Nedimovic; Harold Tobin; Ben Norvell; Glenn Spinelli (Geochemistry, Geophysics, Geosystems)
Abstract Oceanic plate seamounts are believed to play an important role in megathrust rupture at subduction zones, although consistent relationships between subducting seamounts and plate interface seismicity patterns are not found. While most studies focus on impacts linked to their topography, seamounts are also sites of heterogeneity in incoming plate sediments that may contribute to megathrust properties. Here, we characterize incoming plate sediments along the Cascadia subduction zone using new high‐resolution seismic images and compressional wave (Vp) models from the CASIE21 multi‐channel‐seismic experiment. Nine fully‐to‐partially buried seamounts are identified seaward of the deformation front within a region of thick Plio‐Pleistocene sediment where the Juan de Fuca plate is bending into the subduction zone. Anomalously high Vp sediment blankets two seamounts offshore Washington‐Central Oregon, with wavespeeds reaching 36% and 20% higher than adjacent sediment. Fluid seepage and temperatures warm enough for smectite diagenesis extending to shallow depths are inferred from heat flow studies and we attribute Vp anomalies to sediment cementation linked primarily to smectite dehydration. Signatures of fluid seepage above seamounts are also identified offshore Vancouver Island, but anomalously low Vp sediment below distinct reverse polarity reflections are found, indicating trapped fluids, and cooler basement temperatures are inferred. Landward of one seamount, a zone of enhanced sediment compaction is found, consistent with the predicted stress modulating effects of seamount subduction. These new findings of variations in sediment diagenesis and strength around seamounts prior to subduction may contribute to the diverse megathrust frictional properties and seismicity patterns evident at subducting seamounts.